2019
DOI: 10.1002/jctb.6161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic matters in domestic wastewater on lipid/carbohydrate production and nutrient removal of Chlorella vulgaris cultivated under mixotrophic growth conditions

Abstract: BACKGROUND: The combination of wastewater treatment and algal biofuel production has received increasing attention in recent years owing to its many advantages. In order to clarify the influence of different organic pollutants such as carbohydrates, volatile fatty acids (VFAs) and proteins in domestic wastewater on the cultivation of Chlorella vulgaris, three simulated domestic sewages containing glucose, sodium acetate (NaAc) and protein respectively were prepared in this study to culture C. vulgaris in mixot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…The enhanced carbohydrate accumulation can also be partly accredited to the carbonaceous matters present in the wastewater, which was indicated by the TOC, BOD, and COD values. These observations are in agreement with the study of Peng et al 56 , where increased carbohydrate content of Chlorella vulgaris was reported under the mixotrophic growth condition using organic matters in the domestic wastewater. The elevated cellular carbohydrate content using AD medium, thus, compensated for the reduced biomass yield of the test cyanobacterium.…”
Section: Discussionsupporting
confidence: 94%
“…The enhanced carbohydrate accumulation can also be partly accredited to the carbonaceous matters present in the wastewater, which was indicated by the TOC, BOD, and COD values. These observations are in agreement with the study of Peng et al 56 , where increased carbohydrate content of Chlorella vulgaris was reported under the mixotrophic growth condition using organic matters in the domestic wastewater. The elevated cellular carbohydrate content using AD medium, thus, compensated for the reduced biomass yield of the test cyanobacterium.…”
Section: Discussionsupporting
confidence: 94%
“…Similar results were also obtained for protein content analysis (19.66% to 26.03%) (Figure 1D). With the addition of bicarbonate, the increased C/N ratio results in more lipid and carbohydrate biosynthesis for carbon storage with the excess energy (Peng et al, 2019;Singh et al, 2022;Xie et al, 2022). Although the lipid accumulation and protein biosynthesis present competitive relationships with each other, the increased profile of both lipid and protein content were observed in this study, possibly owing to the modified nitrogen content (750 mg/L), which was 10-fold higher than f/ 2 medium and promotes more intracellular conversion to protein (Vishwakarma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Organic carbon sources have a great influence on nutrient removal in mixotrophic cultivation. Peng et al [56] observed that nitrogen and phosphorus removal was better when supplemented with the mixotrophic culture of Chlorella vulgaris with glucose rather than protein or sodium acetate. Addition of glucose also enhanced the fixation of nitrogen and phosphorus in an artificial wastewater [57].…”
Section: Mixotrophic Cultivation Of Algaementioning
confidence: 99%